Implikasi Hukum dan Perlindungan Hak Karyawan dalam Ketidakjelasan Status Pasca Berakhirnya Kontrak Kerja - Khoirun Nisa, Ardina; Zulfahmi (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
This paper analyzes the legal implications of unclear employee work status after the end of a Specific Time Work Agreement (PKWT) in Indonesia, as well as the protection of employee rights. The increasing use of PKWT as a form of flexible employment relationship often creates uncertainty about employee status after the contract ends, which affects employee welfare and creates legal risks for companies. This research aims to examine legal protection for post-contract PKWT employees, as well as the impact of unclear status on the company's welfare and compliance with employment law. The approach used is normative juridical and empirical. Through a normative juridical approach, this research examines legal regulations regarding PKWT, while an empirical approach explores facts in the field regarding the legal protection that employees receive. The research results show that there is a gap between applicable regulations and practice in the field. Even though the law regulates PKWT limits, many companies do not comply with these provisions, so employees often do not receive legal certainty after the contract ends. The conclusion confirms that legal protection for PKWT employees in Indonesia is still weak, especially regarding certainty of status after the contract ends. The suggestions given are increasing government supervision of the implementation of PKWT and revising stricter policies to ensure employee protection in accordance with the law.